2016
DOI: 10.1136/bjophthalmol-2015-307486
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of selective laser trabeculoplasty

Abstract: Repeat SLT can restore IOP control in eyes with open-angle glaucoma that have previously undergone successful initial SLT. Repeat SLT achieves comparable absolute level of IOP control achieved by initial SLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 18 publications
2
43
0
2
Order By: Relevance
“…Looking close at the more recent literature, one can note several studies showing that SLT can be repeated with similar efficacy when compared to the first SLT treatment. In these studies, POAG patients presented a significant IOP reduction at 1 (46) , 4 (47) , 6 (46) , 12 (19,48) , 15 (46) , and 24 months after repeating SLT (26,49) . Corroborating these findings, Gandolfi and Ungaro demonstrated that repeated low power SLT as initial treatment postponed the initiation of medical therapy by a mean time of 6.2 years in patients with OHT (19) .…”
Section: Safety Duration and Repeatabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Looking close at the more recent literature, one can note several studies showing that SLT can be repeated with similar efficacy when compared to the first SLT treatment. In these studies, POAG patients presented a significant IOP reduction at 1 (46) , 4 (47) , 6 (46) , 12 (19,48) , 15 (46) , and 24 months after repeating SLT (26,49) . Corroborating these findings, Gandolfi and Ungaro demonstrated that repeated low power SLT as initial treatment postponed the initiation of medical therapy by a mean time of 6.2 years in patients with OHT (19) .…”
Section: Safety Duration and Repeatabilitymentioning
confidence: 99%
“…This procedure-related complication is influenced by technique and laser burns position (higher risk when laser is applied too posteriorly). Moreover, we believe that the ease of application (outcomes of physicians in training are comparable to those of glaucoma specialists) (25) and the possibility of repeating the procedure with relatively good success rates (in cases with good response to the first SLT treatment) (20,26) are two important advantages of SLT over ALT treatment. These factors have certainly contributed to the shift towards SLT use in the past decade and might explain the reason why ALT has not taken its place as a first line therapy.…”
Section: Laser Trabeculoplasty As Initial Treatment For Open Angle Glmentioning
confidence: 99%
“…The procedure may address issues with topical medication compliance and side effects [1], and it is considered a cost-effective treatment [2]. Although the effect of SLT wanes over time, repeating the procedure may lead to clinical success comparable to that achieved with the initial treatment [35]. …”
Section: Introductionmentioning
confidence: 99%
“…Efficacy results were similar to those achieved with ALT, with waning efficacy and a 50% failure rate after 2 years. The potential repeatability of SLT is thought to be one of its advantages over ALT [5], which was shown to have a success rate of only 14% after re-treatment [7]. …”
Section: Introductionmentioning
confidence: 99%
“…The incidence of iritis, post-laser IOP spikes, and peripheral anterior synechiae is significantly reduced with SLT compared to ALT [71][72][73]. Furthermore, the lack of trabecular meshwork scarring makes SLT more amenable to repeat treatment [4,[74][75][76][77].…”
Section: Selective Laser Trabeculoplasty As Initial Treatmentmentioning
confidence: 99%